1995
DOI: 10.1021/j100020a059
|View full text |Cite
|
Sign up to set email alerts
|

99Mo(.beta.-)99Tc Spectroscopy of MoS2, Lithiated MoS2, Co0.5MoS2, and MoS2 Surface Species

Abstract: Nuclear quadrupole interactions (NQI) were measured for several molybdenum-sulfur compounds by time differential perturbed angular correlation (TDPAC) spectroscopy using the 99Mo@-)99Tc probe. Compounds having the composition MoS2 of different origins and having different degrees of crystallinity, Li-intercalated MoS2, C00.5MoS2, and exfoliated single MoS2 slabs, were investigated. Crystalline and well-ordered 2H-MoS2 exhibits a characteristic NQI-frequency of 11 1 Mrads and axial symmetry. Dispersed MoSz prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…95,96 X-ray investigations on colloid MoS 2 layers prepared by exfoliation of lithium-intercalated molybdenum disulfide in polar solvents 97 showed that the single MoS 2 layers exhibit distorted octahedral coordination with a (2 × 1) superlattice; 98 nuclear quadrupole interaction measurements revealed coordinatively unsaturated Mo sites (sulfur vacancies) at the prismatic sites of the MoS 2 slabs. 99 The direct intercalation of polyaniline via colloid suspensions into MoS 2 has been reported (Figure 6). 83 Recently it was shown that in situ formation of polypyrrole/MoS 2 can be achieved via an oxidative encapsulation reaction and polymer growth under kinetically restricted conditions.…”
Section: Colloid Systemsmentioning
confidence: 95%
“…95,96 X-ray investigations on colloid MoS 2 layers prepared by exfoliation of lithium-intercalated molybdenum disulfide in polar solvents 97 showed that the single MoS 2 layers exhibit distorted octahedral coordination with a (2 × 1) superlattice; 98 nuclear quadrupole interaction measurements revealed coordinatively unsaturated Mo sites (sulfur vacancies) at the prismatic sites of the MoS 2 slabs. 99 The direct intercalation of polyaniline via colloid suspensions into MoS 2 has been reported (Figure 6). 83 Recently it was shown that in situ formation of polypyrrole/MoS 2 can be achieved via an oxidative encapsulation reaction and polymer growth under kinetically restricted conditions.…”
Section: Colloid Systemsmentioning
confidence: 95%
“…The time differential observation of the perturbed angular correlation of g rays emitted from radioactive nuclei (TDPAC) [368,370,371] is a g-spectroscopic technique which also allows the determination of hyperfine interactions such as nuclear electric quadrupole interactions (NQI). The NQI parameters enable local structural information around the g emitter to be extracted.…”
Section: Local Environment Of Elementsmentioning
confidence: 99%
“…Therefore, the NQI exhibits axial symmetry. Such high-frequency components have also frequently been observed in highly disperse MoS 2 powders and in surface species obtained by sulfidation of oxidic precursors [49]. As the particle size decreases, this precession frequency decreases by almost a factor of two for particles of about 50Å diameter.…”
Section: B Frozen Molybdate Solutionsmentioning
confidence: 52%